Green Energy Advances - Enescu, Diana (IntechOpen, 2019)
This book contributes to understanding the development and application of green energy solutions. The term "green energy" is widely used today to indicate sustainable energy sources with zero or minimal environmental and economic impact, obtained from various renewable energy sources. The contents presented in this book deal with different solutions, from small-scale applications (thermoelectric energy harvesting) to energy efficiency in buildings with local renewable energy production (also in critical seismic sites), local energy systems (smart energy management of storage and complex interactions), exploitation of biomasses from agricultural wastes, and voluntary certifications associated with energy trading in large energy systems. These aspects mark a more sustainable evolution of the society with wider green energy usage.